"I am berated as a Communist because I sometimes wear a red tie": Not Forgetting the Awkward Afrikaner, Dr Petronella "Nell" van Heerden. (1st September 2020) - van der Westhuizen, Christi
Abstract: This article explores the shifts in (in)visibility of one of the few "leftist" female Afrikaner public intellectuals in twentieth-century South Africa. The Afrikaner nationalist embrace of Dr. Petronella "Nell" van Heerden (1887–1975), the country's first woman gynecologist, soon turned into marginalization, showing the limits of colonial white dissidence.